Socialno podjetništvo v Sloveniji : pravni in ekonomski vidiki - Elizabeta Zirnstein; Tina Bratkovič Kregar (LeXonomica, 2021)
Social entrepreneurship in Slovenia : legal and economic aspects. The article analyses the effectiveness of social entrepreneurship in Slovenia from legal and economic aspect. The legal aspect deals with the legal environment for establishment and operation of social enterprises, as regulated in the Law on social entrepreneurship, The economic aspect is dedicated to analysis of the economic measures, policies and state incentives, intended to maximise the growth and development of social entrepreneurship in Slovenia. Although social entrepreneurship in other countries has become an important generator of regional and local development, the positive effects of social entrepreneurship in Slovenia are not very significant. Authors of the article point to the administrative barriers for the creation or transformation of social enterprises, but are of opinion that the deficiencies in the Law on social entrepreneurship cannot be a reason for the low number of social enterprises in Slovenia. Authors identify that the problem is mainly in the ineffective implementation of the law, which foresees a number of measures for the promotion of social entrepreneurship, which were not realised. Other reasons are also a poor knowledge and understanding of the concept of social entrepreneurship, insufficient cooperation between the institutions responsible for the development of social entrepreneurship at the national and regional level and the lack of financial mechanisms for financing the investments in social enterprises.Povzetek. Prispevek analizira učinkovitost socialnega podjetništva v Sloveniji z dveh vidikov: pravnega in ekonomskega. Pravni vidik analizira pravno ureditev ustanavljanja in delovanja socialnih podjetij, kot je urejena v Zakonu o socialnem podjetništvu, ekonomski vidik pa ekonomske ukrepe, politiko in državne spodbude, namenjene za čim večjo rast in razvoj socialnega podjetništva v Sloveniji. Čeprav je socialno podjetništvo v tujini postalo pomemben generator regionalnega in lokalnega razvoja, pozitivni učinki socialnega podjetništva v slovenskem prostoru še niso dosegli želene razsežnosti. Avtorici svojo kritiko slovenske ureditve socialnega podjetništva usmerjata predvsem v administrativne ovire za ustanavljanje ali preoblikovanje socialnih podjetij. Kljub pomanjkljivostim pravne ureditve pa ta sama po sebi ne more biti razlog za nizko število socialnih podjetij v Sloveniji. Avtorici ugotavljata, da je problem predvsem v neučinkoviti implementaciji zakona, ki predvideva številne ukrepe za spodbujanje socialnega podjetništva, ki so v veliki meri ostali zgolj mrtva črka na papirju. Razlogi so tudi v slabem poznavanju in razumevanju koncepta socialnega podjetništva, nezadostnem sodelovanju med institucijami, odgovornimi za razvoj socialnega podjetništva na državni in regionalni ravni, ter pomanjkanju finančnih mehanizmov za financiranje naložb v socialna podjetja.